Short-term effects on heart rate variability of occipito-mastoid suture normalization in healthy subjects - Besson, Cyril; Mur, Thierry; Benaim, Charles; Schmitt, Laurent; Gremeaux, Vincent (Frontiers in Neuroscience, 2023)
Occipito-mastoid structure normalization (OMSN) is an osteopathic manipulative treatment aimed at reducing tension around the jugular foramen, where cranial nerves IX, X, and XI exit the skull. The purpose of this study was to observe how heart rate variability (HRV), a marker of autonomic cardiac regulation, was modulated after an OMSN vs. a sham technique (SHAM). Pre- and post-intervention HRV was analyzed in two randomly chosen groups of 15 participants (OMSN vs. SHAM group). HRV was collected in the supine position 5 min before and 5 min after a 10-min application of either OMSN or SHAM. The time and group effect was analyzed using a two-way ANOVA. Independently from group intervention, a significant time effect induced increased HRV. No group effect differences were observed. Multiple comparisons for time and group interaction showed that the root mean square of successive differences (RMSSD), a vagally mediated HRV variable, increased to a greater extent for the OMSN group (p = 0.03) than for the SHAM group. However, both OMSN and SHAM techniques had a significant effect on HRV. Compared to a SHAM technique, OMSN had a significant effect on HRV vagally related metric RMSSD in the short term. We conclude that 10 min of OMSN may be used to induce a short-term influence on parasympathetic autonomic nervous system modulations.